Emergence of HCV Resistance-Associated Variants in Patients Failing Sofosbuvir-Based Regimens: An Observational Cohort. Issue 7 (October 2016) - André-Garnier, Elisabeth; Ribeyrol, Olivier; Gournay, Jerome; Besse, Bernard; Coste-Burel, Marianne; Mabille-Archambeaud, Isabelle; Billaud, Eric; Biron, Charlotte; Pineau, Solene; Raff, François; Imbert-Marcille, Berthe-Marie
Background: Real-life effectiveness data of new hepatitis C direct-acting antivirals are now required. The present study aims to assess the rate of sustained viral response (SVR) and virological failure (VF) in patients infected with chronic HCV treated with sofosbuvir (SOF)-based regimens in routine medical practice. Methods: This observational study included a total of 106 patients infected with HCV genotypes (G)1–4, who initiated SOF-based regimens in 2014. Viral load was followed at baseline, week (W)2, W4, W12 (or W24) and W12 post-treatment. For all VFs, resistance-associated variants (RAVs) were determined at baseline and failure by sequencing of NS5A, NS5B and/or NS3 genes, using the Sanger method. Results: SVR rate was 85% for the whole cohort, 91% for the patients who underwent the full treatment course. The distribution of HCV genotypes was as follows: G1 n =66 (1a=33, 1b=29; 62%), G2 n =8 (8%), G3a n =20 (19%) and G4 n =12 (11%). The main regimens used were SOF+daclatasvir (37%), SOF+ribavirin (33%), SOF+simeprevir (26%) and SOF+ledipasvir (3%). Twenty-five (23%) patients were HIV-coinfected and 1 was HBV-coinfected. Seventy (65%) patients had a prior treatment experience. All VF were relapses ( n =9): 3 G1a, 1 G2, 4 G3a and 1 G4, and mutations conferring resistance to NS5A inhibitors were found but none for NS5B polymerase inhibitors. Conclusions: In a real-life context, the rate of SVR in DAA-treated HCV-infected patients is close to clinical Phase III trial results. RAVs emerged for all patients treated by the anti-NS5A daclatasvir, and persisted several weeks after the end of treatment.